2021
DOI: 10.1108/jrim-05-2020-0107
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing resilience to negative information in consumer-brand interaction: the mediating role of brand knowledge and involvement

Abstract: Purpose This study aims to examine the relationships between the online communities’ characteristics and resilience to negative information (RNI) mediated by both brand knowledge and brand involvement. Design/methodology/approach According to stimulus-organism-response (S-O-R) framework, this research postulates that information quality, rewards and virtual interactivity drive RNI directly and indirectly through brand knowledge and/ or brand involvement. A survey of 326 Facebook pages followers was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 102 publications
1
26
0
Order By: Relevance
“…In particular, influencer marketing can help consumers better understand selenium nutrition, increase residents' awareness of health issues, and promote the concept of healthy eating for a healthy lifestyle. Such a KOL campaign with expert knowledge has also been found to be effective in enhancing consumer resistance to negative information regarding healthy food [56]. As our results showed that the knowledge of naturalness and nutritional value facilitates consumer decision-making.…”
Section: Strategic Impactions For Marketers and Policy Makerssupporting
confidence: 52%
“…In particular, influencer marketing can help consumers better understand selenium nutrition, increase residents' awareness of health issues, and promote the concept of healthy eating for a healthy lifestyle. Such a KOL campaign with expert knowledge has also been found to be effective in enhancing consumer resistance to negative information regarding healthy food [56]. As our results showed that the knowledge of naturalness and nutritional value facilitates consumer decision-making.…”
Section: Strategic Impactions For Marketers and Policy Makerssupporting
confidence: 52%
“…eWOM can be linked by electronic loyalty programs (eg via apps), and those who use loyalty apps are more vulnerable to accepting deals (Son et al., 2020, p.835) which BO can deploy to retain existing customers, and attract new ones. Furthermore, previous research finds that virtual interactivity is a driver of brand involvement (Elsharnouby et al., 2021). Loyalty programs (Formanek & Tahal, 2017) can be supplemented with alliance programs of other services such as car parking, hotels and restaurants in this case.…”
Section: Discussion: Resonance At the Operamentioning
confidence: 97%
“…Virtual Communities are groups of people or business partners who interact based on a common interest. Such interactions are at least partly supported and/or mediated by technology and guided by certain protocols and norms (Elsharnouby et al, 2021). Virtual Communities are formed on the basis of a common interest in a product category (cars and cameras), hobbies (rock climbing, music, and chess), or life situations (pension, illness, and pregnancy) (Amoncar, 2020).…”
Section: Virtual Communitiesmentioning
confidence: 99%
“…Toyota in Makassar City, and its relation tovirtual communitiesas a group that is considered to be related to consumers' purchasing decisions indirectly in choosing or meeting their needs for Toyota products. Many studies directly link Virtual Communities with brand equity and brand equity on purchasing decisions (Elsharnouby et al, 2021;Hollebeek et al, 2017;Ko et al, 2018). What is renewed in this research is to see the indirect relationship of the influence of Virtual Communities on purchasing decisions where there is brand equity as a mediating.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation